Epidemiological and clinical characteristics of COVID-19 reinfection during the epidemic period in Yangzhou city, Jiangsu province - Wang, Yin; Liang, Jie; Yang, Huimin; Zhu, Liguo; Hu, Jianli; Xiao, Lishun; Huang, Yao; Dong, Yuying; Wu, Cheng; Zhang, Jun; Zhou, Xin (Frontiers in Public Health, 2023)
Background Reinfection had occurred in previously infected individuals, caused waves of epidemic in many countries. Therefore, we aimed to explore the characteristics of COVID-19 reinfection during the epidemic period in Yangzhou, and provide basis for assessing the COVID-19 situation and optimizing the allocation of medical resources. Methods We choosed previously infected individuals of SARS-CoV-2 reported locally in Yangzhou from January 2020 to November 30, 2022. A telephone follow-up of cases was conducted to collect the reinfection information. We conducted a face-to-face survey on cases who met the definition of reinfection to collect information on clinical symptoms, vaccination status and so on. Results Among the 999 eligible respondents (92.24% of all the participants), consisting of 42.28% males and 57.72% females, the reinfection incidence of females was significantly higher than that of male cases (P＜0.05); the ages of the respondents ranged from 1 to 90 years, with the mean age of 42.28 (SD 22.73) years; the most of the sufferers were infected initially with Delta variant (56.88%), followed by the Omicron subvariants BA.1/BA.2(39.52%). Among all the eligible respondents, 126 (12.61%) reported COVID-19 reinfection appearing during the epidemic period, and the intervals between infections were from 73 to 1082 days. The earlier the initial infection occurred, the higher the reinfection incidence, the reinfection incidence was significantly increased when the interval beyond one year(P<0.01). 119 reinfection cases (94.4%) were symptomatic and the most common symptoms included fever (65.54%) and cough (61.34%); compared with the initial infection cases, the proportion of clinical symptoms in the reinfected cases was significantly higher (P<0.01). The reinfection incidence of COVID-19 vaccination groups with different doses was statistically significant (P<0.01), less reinfections were observed among the respondents with 3 doses of COVID-19 vaccination compared to the respondents with two doses( 2 =14.595, P<0.001) or without COVID-19 vaccination( 2 =4.263, P=0.039). Conclusion The reinfection incidence varied with different types of SARS-CoV-2 strains. The reinfection incidence was influenced by various factors such as virus characteristics, vaccination, epidemic prevention policies, and individual variations. As the SARS-CoV-2 continues to mutate, vaccination and appropriate personal protection have practical significance in reducing the risk of reinfection.